Tokoh Sufi Wanita RabiAh Al - Adawiyyah: Motivator ke Arah Hidup Lebih Bermakna - Saari, Che Zarrina (Jurnal Usuluddin, 2007)
Rabiah al-Adawiyyah was a Sufi figure known by eastern and western scholars and Sufism supporters through her concept of Love of God, asceticism, fear of God, piety and her interesting poems and anecdotes. Nevertheless, not many of them discussed about her mystical experiences from psychological view in motivating human life towards meaningful life. Thus this article will try to highlight who is Rabiah al-Adawiyyah, what are the concepts of Sufism introduced by her, which are of her poems and anecdotes influenced the readers and what are the motivational design can be developed through her mystical experiences in enhancing todays human life towards meaningful life in order to attain the happiness in this world and the hereafter.